A new exon 12 mutation in the EPAS1 gene possibly associated with erythrocytosis. (16th May 2019) - Schelker, Roland Christian; Herr, Wolfgang; Grassinger, Jochen
Abstract: In secondary erythrocytosis, the elevated red cell count is powered by factors outside the erythroid compartment, for instance by raised erythropoietin (EPO) synthesis based on congenital defects of the oxygen‐sensing pathway. The principal transcriptional regulator of EPO synthesis is endothelial PAS domain‐containing protein 1 (EPAS 1). We present here the first report of a patient with erythrocytosis involving a mutation of amino acid 525 in EPAS1. The p.Asp525His mutation affects a residue that is farthermost from primary functional site Pro‐531 of any of the erythrocytosis‐related mutations that have been identified up to now.